A High-Speed Dynamic Partial Reconfiguration Controller Using Direct Memory Access Through a Multiport Memory Controller and Overclocking with Active Feedback. (17th August 2011) - Hoffman, John C.; Pattichis, Marios S.
Abstract : Dynamically reconfigurable computing platforms provide promising methods for dynamic management of hardware resources, power, and performance. Yet, progress in dynamically reconfigurable computing is fundamentally limited by the reconfiguration time overhead. Prior research in the development of dynamic partial reconfiguration (DPR) controllers has been limited by its use of the Processor Local Bus (PLB). As a result, the bus was unavailable during DPR. This resulted in significant time overhead. To minimize the overhead, we introduce the use of a multiport memory controller (MPMC) that frees the PLB during the reconfiguration process. The processor is thus allowed to switch to other tasks during the reconfiguration operation. This effectively limits the reconfiguration overhead. An interrupt is used to inform the processor when the operation is complete. Therefore, the system can multitask during the reconfiguration operation. Furthermore, to maximize performance, we introduce the use of overclocking with active feedback. During overclocking, the use of active feedback is used to ensure that the device voltage and temperature are within nominal operating conditions. All of these contributions lead to significant performance improvements over current partial reconfiguration subsystems. The portability of the system, demonstrated on the Virtex-4 and the Virtex-5, consists of four different hardware platforms.